Illicit drug use and its association with key sexual risk behaviours and outcomes: Findings from Britain's third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). - Rachelle Paquette; Clare Tanton; Fiona Burns; Philip Prah; Maryam Shahmanesh; Nigel Field; Wendy Macdowall; Kirsten Gravningen; Pam Sonnenberg; Catherine H Mercer (PLoS ONE)
Objectives We explore the hypothesis that using illicit drugs other than, or in addition to, cannabis is associated with sexual risk behaviour and sexual health outcomes in the British population. Methods We analysed data, separately by gender, reported by sexually-active participants (those reporting > = 1 partners/past year) aged 16-44 years (3,395 men, 4,980 women) in Britain's third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a probability survey undertaken 2010-12 involving computer-assisted personal-interview and computer-assisted self-interview. Analyses accounted for the stratification, clustering and weighting of the data. Multivariable logistic regression was used to calculate adjusted odds ratios. Results Use of illicit drugs other than, or in addition to, cannabis in the past year was reported by 11.5% (95%CI:10.4%-12.8%) of men and 5.5% (4.8%-6.3%) of women. Use of these types of drugs was more common among those <35 years, those who reported poor general and/or sexual health behaviours, e.g. binge drinking > = weekly (age-adjusted ORs, aAORs, 10.91 (6.27-18.97) men; 9.95 (6.11-16.19) women); having > = 2 condomless partners in the past year (aAOR:5.50 (3.61-8.39) men; 5.24 (3.07-8.94) women). Participants reporting illicit drug use were more likely (than those who did not) to report sexual health clinic attendance (ORs after adjusting for age, sexual identity and partner numbers: 1.79 (1.28-2.51) men; 1.99 (1.34-2.95) women), chlamydia testing (1.42 (1.06-1.92) men; 1.94 (1.40-2.70) women), unplanned pregnancy (2.93 (1.39-6.17) women), and among men only, sexually transmitted infection diagnoses (3.10 (1.63-5.89)). Conclusions In Britain, those reporting recent illicit drug use were more likely to report other markers of poor general and sexual health. They were also more likely to attend sexual health clinics so these should be considered appropriate settings to implement holistic interventions to maximise health gain.